Advertising and personal selling - Rajput, Namita (Himalaya Pub. House, 2008)
An authentic, simple and crisp presentation of the subject matter.; Various concepts have been explained in a lucid, pragmatic and student friendly language.; Covers the detailed syllabus of Delhi University for the students of B. Com. (H) III year.; Each paragraph is distinctly numbered and starts with relevant background of the subject.; Previous years questions have been given in the appendix for reference.